Schools and their influences on students' ASEAN awareness a study of Quezon City high schools - Andres, Brenson Y.; Santarita, Joefe B.; Andres, Brenson Y. (Quezon City Asian Center, University of the Philippines Diliman, 2018)
Inglehart (1970) argued that formal education is vital in amassing citizens' awareness and support for regional integration. In light of the recently launched ASEAN Community, it is imperative to gauge the ASEAN awareness of Filipino students and evaluate how school-related factors influence such awareness. With grade 10 students in Quezon City as primary respondents, the study aims to : (1) assess the state of respondents' awareness of ASEAN; (2) identify respondents' sources of information on ASEAN; (3) analyze the influence of school-related factors on the respondents' level of ASEAN awareness; and (4) formulate policy recommendations as possible guide for educational institutions to enhance the promotion of ASEAN awareness among the Filipino youth. To fulfill such goals, an explanatory sequential mixed methods design was employed which required two stages of data collection. The quantitative phase was done first through a survey administered to 447 students from nine schools. Results of the survey were utilized to fulfil the first two aims and to select the four schools and specific respondents for the second stage. The qualitative phase was done through focus group discussion with 57 students, interview with nine teachers, and analysis of school curricula and memoranda. Results in this phase were used to address the last two aims and to provide more depth and insight to the quantitative findings. Results of the study showed that respondents possess moderate level of ASEAN awareness, although the weighted mean lies closely at the border of fair and moderate levels. Such fact is somehow mirrored in the focus group discussion where majority of the respondents rated their ASEAN awareness at the fair level. In terms of their sources of information on ASEAN, Internet ranked first followed by television. Even though the school is a frequent source, it only occupied the third spot. Lastly, while the Spearman's ranked-order correlation coefficient disproved the relationship between teacher's ASEAN knowledge and student's ASEAN awareness, qualitative findings revealed that formal curriculum, informal curriculum, and teacher's pedagogy somehow influence student's ASEAN awareness. In general, the study revealed that while there are efforts from ASEAN and from the Philippine government to promote ASEAN, there is still a greater need to increase Filipino citizens' ASEAN awareness, particularly the youth who will play an integral part in the future of the region. It is vital for them to realize that ASEAN is not a mere organization of states but a community that has a direct impact on their lives. In order to accomplish this, a number of recommendations were outlined, such as reforming the formal curriculum, organizing engaging and informative activities in schools, training teachers in ASEAN content and pedagogy, and increasing ASEAN's exposure in other platforms.
Thesis (Master of Arts in Asian Studies)--University of the Philippines Diliman
Keywords: ASEAN; High schools -- Philippines -- Quezon City